Influence of African Atmospheric Rivers on Precipitation and Snowmelt in the Near East's Highlands. Issue 4 (17th February 2021) - Bozkurt, D.; Sen, O. L.; Ezber, Y.; Guan, B.; Viale, M.; Caglar, F.
Abstract: Atmospheric rivers (ARs) traveling thousands of kilometers over arid North Africa could interact with the highlands of the Near East (NE), and thus affect the region's hydrometeorology and water resources. Here, we use a state‐of‐the‐art AR tracking database, and reanalysis and observational datasets to investigate the climatology (1979–2017) and influences of these ARs in snowmelt season (March–April). The Red Sea and northeast Africa are found to be the major source regions of these ARs, which are typically associated with the eastern Mediterranean trough positioned over the Balkan Peninsula and a blocking anticyclone over the NE‐Caspian region, triggering southwesterly air flow toward the NE's highlands. Approximately 8% of the ARs are relatively strong (integrated water vapor transport >∼275 kg m −1 s −1 ). AR days exhibit enhanced precipitation over the crescent‐shaped orography of the NE region. Mean AR days indicate wetter (up to + 2 mm day −1 ) and warmer (up to + 1.5°C) conditions than all‐day climatology. On AR days, while snowpack tends to decrease (up to 30%) in the Zagros Mountains, it can show decreases or increases in the Taurus Mountains depending largely on elevation. A further analysis with the observations and reanalysis indicates that extreme ARs coinciding with large scale sensible heat transport can significantly increase the daily discharges. These results suggest that ARs can have notable impacts on the hydrometeorology and water resources of the region, particularly of lowland Mesopotamia, a region that is famous with great floods in the ancient narratives. Plain Language Summary: Atmospheric rivers (ARs) are important components of the global water cycle as they are responsible for over 90% of the poleward moisture transport at middle to high latitudes. ARs mostly prevail over the oceans and primarily landfall on the western coasts of the midlatitude continents as a result of westerly flow of the midlatitudes. Apart from the large ocean basins, certain ARs can develop and propagate over continents, which has received less scientific attention. In this respect, this study aims to show how overland African ARs developing in the snowmelt season can influence the Near East's highlands, which are essential for satisfying the water need of lowland areas of Mesopotamia that are potentially at risk of water scarcity and conflicts. We show that mean AR days lead to wetter and warmer conditions than a typical day in the snowmelt season. On AR days, while snowpack tends to decrease (up to 30%) in the Zagros Mountains, it can show decreases or increases in the Taurus Mountains depending largely on elevation. We emphasize that the poleward warm air advection and moisture transport toward the Near East within ARs can have profound impacts on the water resources of the region. Key Points: African atmospheric rivers (ARs) can transport tropical humid air towards the Near East in the snowmelt season The region is wetter and warmer on AR days compared to all‐day climatology, causing changes in snowpack depending on elevation Extreme ARs accompanied by large scale sensible heat transport cause significant rises in river discharges in the region